A study of association of the complement C4 mutations with systemic lupus erythematosus in the Malaysian population - Puah, S.M.; Lian, L.H.; Chew, C.H.; Chua, K.H.; Tan, S.Y. (2007)
The aim of the present study was to investigate the association of C4 gene mutations with systemic lupus erythematosus, in 130 Malaysian SLE patients and 130 healthy controls. Generally, various PCR approaches were used to screen the mutations of the C4 genes, which included 2 bp (+TC) insertions at codon 1213 in exon 29, 1 bp deletions (-C) at codon 811 in exon 20, 1 bp (-C), 2 bp (-GT) deletions at codons 522 and 497 in exon 13 and null alleles. No mutations located at exons 13, 20 and 29 of the C4 gene, were detected amongst the patient and control samples in this study. C4A*Q0 was found in two out of the 130 control samples, while C4B*Q0 was present in two out of the 130 SLE patients. Overall, our results do not demonstrate a significant association to these known C4 mutations identified by previous studies, in the Malaysian scenario.